Punctuated Equilibrium and the Supreme Court. Issue 4 (November 2013) - Robinson, Rob
<x xml:space="preserve">Abstract</x> In the legislative and executive branches, policy scholars have used punctuated equilibrium (PE) theory to describe and explain patterns of change. However, there has been little examination of how PE might apply to courts and legal policy change. This article addresses that gap by providing evidence that legal policy change—here conceptualized as changes in what precedents the Supreme Court most often cites—is governed by PE theory. After making a prima facie case for the applicability of PE theory to the Court, I leverage network rankings of Supreme Court decisions to create a proxy for legal policy change that improves on existing measures. Using both a stochastic process model and an analysis of the punctuations the measure uncovers, I find strong evidence of PE processes.